Answer:
3. D) [tex](-8, -17)[/tex]
2. D) [tex](-15, -16)[/tex]
1. B) [tex](3, -4)[/tex]
Step-by-step explanation:
3.
{y = 3x + 7
{y = x - 9
x - 9 = 3x + 7
-3x - 3x
____________
−2x - 9 = 7
+ 9 + 9
__________
−2x = 16
____ __
−2 −2
[tex]-8 = x[/tex][Plug this back into both equations above to get the y-coordinate of −17]; [tex]-17 = y[/tex]
__________________________________________________________
2.
{−4x + 3y = 12
{−2x + 3y = −18
−½[−4x + 3y = 12]
{2x - 1½y = −6 >> New Equation
{−2x + 3y = −18
_______________
1½y = −24
____ ____
1½ 1½
[tex]-16 = y[/tex][Plug this back into both equations above to get the x-coordinate of −15]; [tex]-15 = x[/tex]
__________________________________________________________
1.
{−10x - 3y = −18
{−7x - 8y = 11
−⅜[−7x - 8y = 11]
{−10x - 3y = −18
{2⅝x + 3y = −4⅛ >> New Equation
_________________
−7⅜x = −22⅛
______ _____
−7⅜ −7⅜
[tex]3 = x[/tex][Plug this back into both equations above to get the y-coordinate of −4]; [tex]-4 = y[/tex]
I am joyous to assist you anytime.